Juridical discourse: problems and prospects - Rakhmetova, A.T. (KSU Publ., 2018)
In modern linguistic science the discourse is understood as the difficult phenomenon consisting of participants of communication, situation of communication and the text. In other words, the discourse is an abstract invariant description of the structural-semantic signs realized in concrete texts. The nature of legal discourse is considered in the article. The juridical text is not in this sense an exception as the polysemy and homonymy of semantics are inherent in it that generates impossibility of accurate and correct interpretation of the text on law and, in turn, causes difficulty of understanding of the juridical text by the ordinary native speaker. The author considers various interpretations of the concept of discourse, draws attention to the features of the media discourse, studies the problems and prospects for the development of legal discourse. Investigating the connections, problems and prospects of legal discourse, the author comes to the conclusion that the legal media discourse is one of the most widespread and at the same time little studied modern discourses.
Құқықтық дискурс: мəселелері жəне перспективалары
Юридический дискурс: проблемы и перспективы
Keywords: discourse; media discourse; legal discourse; text; text interpretation